Category-specific fMRI correlates of picture naming: A study with Arabs and Filipinos. (August 2022) - Tayeb, Haythum O.; Alghamdi, Jamaan; Ahmed, Naushad; Alsawwaf, Yousef; Alsafi, Khalid; Baduwailan, Abrar; Yaghmoor, Bassam; Elyas, Tariq; Mudarris, Mohammed; Weisholtz, Daniel S.
Abstract: Cross cultural neuroimaging work has demonstrated differences in neural correlates of some cognitive processes between individuals from different cultures, often comparing American and Chinese subjects. In contrast, a limited number of studies examined Arab and/or Filipino participants. This fMRI study aimed to demonstrate neural activations during animal and tool picture naming by 18 healthy Arabs and 18 healthy Filipino participants. In animal naming contrasted with tool naming, Arabs preferentially activated regions in the right lateral occipital and fusiform cortices, whereas Filipinos recruited bilateral visual areas. Cross-group comparisons of animal naming revealed that Arabs recruited right visual areas more than Filipinos, who in turn recruited the cerebellum more than Arabs. In tool naming, Arabs preferentially activated a predominantly left frontoparietal network, whereas no regions were identified in Filipinos, and no differences in activation between groups were found. Using a low-demand picture-naming task, this study revealed category-specific neural activations during picture naming by Arabs and Filipinos, as well as between-group differences in animal naming. The results suggest that Arabs and Filipinos may have culture-specific differences in processing animate and inanimate pictures, and caution against generalizing findings from the more commonly studied populations, especially in verbal tasks such as picture naming. Highlights: The neural correlates of animal and tool picture naming in Arabs and Filipinos are category specific. Animal naming by Arabs tended to preferentially activate the nondominant ventral visual stream. Tool naming by Arabs activated dominant frontoparietal areas related to praxis. Arabs utilized nondominant visual areas more significantly than Filipinos during tool and animal naming.